PENGARUH LOCAL KNOWLEDGE, DAN SKILLS TERHADAP KINERJA KARYAWAN PADA UMKM DI DESA NGERANGAN KLATEN - David Abdul Kholiq; Bayu Kurniawan; Noni Setyorini (MANABIS: Jurnal Manajemen dan Bisnis, 2023)
This study aims to determine the effect of local knowledge and skills on employee performance in MSMEs in Ngerangan Village, Klaten. The population of researchers is from 28 MSMEs in the village of Ngerangan Jaya Klaten that the total number of employees is 190 employees, the sample that has been determined the sample in this study is 100 drivers using probability sampling techniques with simple random sampling methods using the slovinh formula. Data analysis in this study used the SPSS AMOS 24 program. Hypothesis testing with the AMOS SEM approach. The results of the analysis and discussion show that the influential variable local knowledge affects employee performance, skills affect the performance of MSME employees in Ngerangan Village, Klaten